A feasibility trial of Cogmed working memory training in fragile X syndrome - Au, Jacky; Berkowitz-Sutherland, Laura; Schneider, Andrea; Schweitzer, Julie B.; Hessl, David; Hagerman, Randi (Journal of Pediatric Genetics, 2014)
Individuals with fragile X syndrome (FXS) often present with an array of neurocognitive deficits, particularly in working memory (WM) and other executive functions. Evidence is accumulating that WM training can be effective in certain clinical populations in improving WM abilities and decreasing attention deficit hyperactivity disorder symptoms. We report preliminary findings evaluating the feasibility of Cogmed JM program, a computer-based WM intervention, within the FXS population. Twenty-five participants were evaluated for training. Seventeen were deemed eligible, of whom eight enrolled in the 5-wk training. Baseline characteristics were analyzed, as well as training progress and parental impressions. We conclude that Cogmed JM is a feasible intervention in FXS, though a certain baseline level of ability is required, and urge future controlled trials to determine efficacy.
Keywords: Fragile X syndrome; working memory training; targeted treatments; Cogmed